Assessment of dementia in minority ethnic groups in Europe: a 14-year follow-up survey - Nielsen, T. Rune; de Mendonça, Alexandre; Frölich, Lutz; Engelborghs, Sebastiaan; Gove, Dianne; Lamirel, Daphné; Calia, Clara; Waldemar, Gunhild (International journal of geriatric psychiatry, 2024)
Objectives There is no European consensus on good clinical practice for timely diagnosis and culturally appropriate care of people with dementia from minority ethnic groups. Despite significant advances in culture-sensitive dementia diagnostics, little is known about how this has been implemented in clinical practice. The aims of this follow-up survey were to explore current practices for assessing dementia in patients from minority ethnic groups in Europe and to determine whether barriers in access to specialized dementia services have changed during the last 14 years. Methods A cross-sectional online survey was conducted in the European Alzheimer's Disease Consortium (EADC) in June 2023. The survey utilized questionnaires from a previous EADC survey from 2009 and focused on different points in the clinical assessment of dementia in patients from minority ethnic groups. Results Thirty-three centers from 15 countries participated in the survey, of which 21 were the same as in the 2009 survey. Patients from minority ethnic groups were seen on a regular basis in 91% of these centers, which was a significant increase compared to 2009 (69%, p = 0.04). Despite perceived clinical expertise increasing, implemented strategies for bypassing cultural and linguistic barriers were sparse and communication problems and lack of adequate assessment tools continued to be the main perceived barriers in diagnostic assessment of dementia in minority ethnic groups. Conclusions Patients from minority ethnic groups are increasingly being referred for diagnostic assessment of dementia in Europe. Despite some improvements, diagnostic challenges generally remained the same as in 2009 and there is a continuous need to implement effective cross-cultural communication and assessment practices.